Revitalization of Taman Mini Indonesia Indah (TMII) as an Effort to Develop Tourist Destinations - Maulana, Sendi Rahman; Setianingtyas, Audry; Fatima, Shalisa Syora Diah; Iryawan, Raesya; Nada, Nabila Marsha; Auliya, Anisatul (Institute of Advance Science, Social, and Sustainable Future, 2024)
Background : Taman Mini Indonesia Indah (TMII), located in East Jakarta, is a key cultural tourism destination in Indonesia, displaying the nation’s diverse cultural heritage, architecture, and natural landscapes from across the archipelago. With aging facilities, TMII has initiated revitalization efforts to improve infrastructure, modernize attractions, and enhance visitor engagement. This study aims to evaluate the impact of TMII’s revitalization on its quality as a tourist destination. This research contributes to existing studies on tourism revitalization, focusing on destination development and infrastructure improvements to attract and maintain tourism interest. Methods: This study employs a qualitative approach, analyzing secondary data from books, journals, and websites. Data collection emphasizes literature on tourism revitalization, while descriptive analysis techniques are applied to interpret the data and assess TMII’s revitalization initiatives in relation to sustainable cultural tourism. Findings: Findings reveal that TMII’s revitalization has had a positive impact on infrastructure quality and visitor satisfaction, highlighting the integration of modern technology and environmentally sustainable practices. Upgraded facilities and the implementation of eco-friendly tourism solutions have enhanced TMII’s appeal, supporting its objective to remain a culturally rich and sustainable destination. Conclusion: TMII’s revitalization has successfully reinforced its standing as a high-quality tourist destination, advancing both visitor experience and sustainable practices. Novelty/Originality of this article: This study uniquely examines TMII’s revitalization from the perspective of sustainable cultural tourism, underscoring the role of modern infrastructure and eco-friendly initiatives in maintaining a culturally significant destination.